Influence of the Connector and Implant Design on the Implant-Tooth-Connected Prostheses - da Silva, Edmar Ferreira; Pellizzer, Eduardo Piza [UNESP]; Mazaro, José Vitor Quinelli [UNESP]; Garcia, Idelmo Rangel [UNESP] (Wiley-Blackwell, 2010)
Purpose:The purpose of this study was to evaluate stress transfer patterns between implant-tooth-connected prostheses comparing rigid and semirigid connectors and internal and external hexagon implants.Materials and Methods:Two models were made of photoelastic resin PL-2, with an internal hexagon implant of 4.00 x 13 mm and another with an external hexagon implant of 4.00 x 13 mm. Three denture designs were fabricated for each implant model, incorporating one type of connection in each one to connect implants and teeth: 1) welded rigid connection; 2) semirigid connection; and 3) rigid connection with occlusal screw. The models were placed in the polariscope, and 100-N axial forces were applied on fixed points on the occlusal surface of the dentures.Results:There was a trend toward less intensity in the stresses on the semirigid connection and solid rigid connection in the model with the external hexagon; among the three types of connections in the model with the internal hexagon implant, the semirigid connection was the most unfavorable one; in the tooth-implant association, it is preferable to use the external hexagon implant.Conclusions:The internal hexagon implant establishes a greater depth of hexagon retention and an increase in the level of denture stability in comparison with the implant with the external hexagon. However, this greater stability of the internal hexagon generated greater stresses in the abutment structures. Therefore, when this association is necessary, it is preferable to use the external hexagon implant.
Keywords: dental implant; implant design; photoelasticity; tooth-implant connection